Crowd4U: An Initiative for Constructing an Open Academic Crowdsourcing Network - Morishima, Atsuyuki; Amer-Yahia, Sihem; Roy, Senjuti (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
We describe the Crowd4U initiative, which aims at constructing an all-academic open and generic platform for microvolunteering and crowdsourcing worldwide. Crowd4U provides a microtask-based platform in which most workers are volunteers at universities and other research institutions. Crowd4U is open in the sense that the platform can interact with other platforms, researchers can register their tasks, and the underlying code is not a black box. It is generic as it allows to register virtually any task. Crowd4U has already been used by several projects for public and academic purposes.